2006
DOI: 10.1152/japplphysiol.01349.2005
|View full text |Cite
|
Sign up to set email alerts
|

A simplified noninvasive method to measure airway blood flow in humans

Abstract: Our laboratory has previously developed and validated a noninvasive soluble gas uptake method to measure airway blood flow (Qaw) in humans (Onorato DJ, Demirozu MC, Breitenbücher A, Atkins ND, Chediak AD, and Wanner A. Am J Respir Crit Care Med 149: 1132-1137, 1994; Scuri M, McCaskill V, Chediak AD, Abraham WM, and Wanner A. J Appl Physiol 79: 1386-1390, 1995). The method has the disadvantage of requiring eight breath-hold maneuvers for a single Qaw measurement, a complicated data analysis, and the inhalation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] However, an in vitro study has demonstrated potency diff erences among diff erent glucocorticosteroids. 17 In a meta-analysis, Rodrigo 18 reviewed the rapid clinical eff ects of ICSs in acutely exacerbated asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16] However, an in vitro study has demonstrated potency diff erences among diff erent glucocorticosteroids. 17 In a meta-analysis, Rodrigo 18 reviewed the rapid clinical eff ects of ICSs in acutely exacerbated asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Predicted normal values for FEV 1 were taken from Crapo et al 8 Qaw was measured with a noninvasive, previously validated soluble inert gas uptake method. 9,10 The method determines the uptake of dimethyl ether (DME) from the anatomic dead space during breath holds of diff erent duration. From the decrease in expired DME concentration over time, DME uptake is obtained, and from it Qaw is calculated using Fick's principle.…”
Section: Measurementsmentioning
confidence: 99%
“…Several studies in humans have addressed the effects of ICS on blood flow in the bronchial mucosa [1,18], where data on perfusion of the bronchial tree have been derived from the measured disappearance of an inhaled inert gas from the airways (exhaled air) into the tracheo-bronchial circulation [1]. However, fewer clinical studies have addressed a possible effect of ICS on the pulmonary circulation.…”
Section: Discussionmentioning
confidence: 99%
“…To assess airway vascular relaxation responses, we determined Q aw, an index of airway vascular smooth muscle tone. Q aw was measured with a previously validated soluble inert-gas uptake method, normalized for the anatomical dead space, and expressed as microliters per minute per milliliter (27,29). FEV in 1 s (FEV 1) was measured with a Koko spirometer (Ferraris Respiratory, Louisville, CO).…”
Section: Subjectsmentioning
confidence: 99%